Differential effects of pore structure of mineral and maceral components on the methane adsorption capacity evolution of the lower jurassic Da'anzhai member of the Ziliujing Formation lacustrine shale, Sichuan Basin, China. (January 2023) - Xiong, Shuling; Gao, Zhiye; Wei, Weihang; Wang, Yaohua
Abstract: Adsorbed gas makes a great contribution to shale gas reserves. During the geological evolution process, it is of prominent significance to clarify the dynamic evolution mechanism of methane adsorption capacity (MAC) of shale to enhance exploration. Variations of the pore structure and surface properties of shales lead to their different MAC. However, the pore structure characteristics and the evolution mechanism of different maceral and mineral components is different. The co-evolution modes and influence mechanism on the MAC of shale remains poorly understood. Therefore, in order to investigate the influential relationship between pore structure evolution and MAC of shales, methane adsorption experiments were conducted on a series of shale samples with the same composition at different thermal maturities. In addition, the original components of the shale sample were analyzed by measuring total organic carbon (TOC) content and mineral composition. Pore structures of the four shale samples were characterized by N2 adsorption, high-pressure mercury intrusion porosimetry (HPMIP), and digital analyses of field-emission scanning electron microscopy (FE-SEM). The results showed a good correlation between the APpore (apparent porosity of pore) of organic pores with the size ranging from 10 to 30 nm and MAC (R 2 = 0.943), confirming the prominent influence of organic pores on the MAC of shale. In addition, the APpore of pores within 10–30 nm and aspect ratio of secondary organic matter with spongy pores are highly correlated with MAC (R 2 are 0.833 and 0.811, respectively), which suggests that secondary organic matter with spongy pores have a crucial influence on MAC. Clay mineral pores with a pore size of 10–30 nm also effect the MAC of shale. A large number of clay mineral microfractures, with a scale of less than 200 nm, appear to effectively connect organic pores, providing a viable mechanism for hydrocarbon migration and enhancing the MAC of shale. Siliceous mineral dissolution pores and microfractures are not conducive to hydrocarbon migration due to their inability to form effective connections with organic pores and fractures and showing a weak correlation with MAC. The outcome of this study elucidates the main controlling mechanism affecting methane adsorption behavior of continental shale reservoirs and provides a path for the efficient exploration and evaluation of shale gas under actual geological conditions. Highlights: An identification method is innovated to distinguish pores and fractures. The secondary organic matter with spongy pores makes a main contribution to shale MAC. A coupling model of shale pore evolution and MAC evolution is proposed.